Examining the indirect effects of kindergarteners' executive functions on their academic achievement in the middle grades of elementary school. Issue 10 (27th July 2022) - Nakamichi, Naoko; Nakamichi, Keito; Nakazawa, Jun
ABSTRACT: We investigated whether the cool and hot executive functions (EFs) exhibited by kindergarteners could predict their academic achievement in the middle grades of elementary school. The study assessed the cool and hot EF of 48 Japanese kindergartners ( M = 78.12 months) and then measured these same children's academic achievement in language and mathematics between grades one to four. The study's confirmative factor analysis indicated that early childhood EFs have both cool and hot factors. Its structural equation modeling revealed that although both cool and hot early childhood EFs can directly predict academic achievement in grade one, cool EFs had a greater predictive effect. It also found that cool and hot early childhood EFs had an indirect effect on academic achievement between grades two to four insofar as children's academic achievement in grades two to four was predicted sequentially by their previous academic achievements.